Knowledge-based urban development Planning and applications in the information era - Yigitcanlar; Velibeyoglu; Baum (Information Science Reference, 2008)
"This book covers theoretical, thematic, and country-specific issues of knowledge cities to underline the growing importance of KBUD all around the world, providing substantive research on the decisive lineaments of urban development for knowledge-based production (drawing attention to new planning processes to foster such development), and worldwide best practices and case studies in the field of urban development"--Provided by publisher.